Hospital cleaners’ knowledge, attitude and practices and the influence of training regarding cleaning roles in two government hospitals in the Erongo Region, Namibia - Geurtze, Etheline Olivia (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2022.